(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The current study aims to compare a number of financial failure models, namely Altman, Sherrod, Kida, Zmijewski, Majewska, and Spring, to analyze the risks of financial failure, and apply them to Wal-Mart Retail Company, a company listed on the New York Stock Exchange since 1972, and demonstrate their importance to the risks of failure. The financial that assists the financial manager in managing it skillfully, which is reflected on the institution itself, as well as on the economic development of all sectors; Therefore, the study aimed to define the most important models of financial failure and to find out their truth and the extent to which they sense the risks of financial failure, and do the models used in the study, the research sample, indicate the risks of expected financial failure to the same degree? Providing information about these models to financial managers, and how to apply them and develop their skills in risk management. One of the most important findings of the study is the lower Z score for the years (2019, 2021, 2021) compared to all previous years and models, although the Z value was outside the failure zone. However, the margin of safety has decreased, which indicates that the company was affected by the Corona epidemic.